A Comparison of Derivational and Inflectional Morphemes between Nusa Penida Dialect and Sepang Dialect - ., Ni Putu Sri Merta Utami; ., Dr. I Gede Budasi,M.Ed,Dip.App.Lin; ., Dewa Putu Ramendra, S.Pd, M.Pd (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
This study aimed at describing the comparison of prefixes and suffixes in Nusa Penida Dialect and Sepang dialect which belong to derivation and inflection. This research was a descriptive qualitative research. Two informants sample of Nusa Penida were chosen based on a set of criteria. The data were collected based on three techniques, namely: observation, recording technique, and interview (listening and noting) technique. The results of the study showed that those ware difference: prefix {mə-}: NPD: tΛlʊh (V) become mΛtΛlʊh (V) and when prefix {mə-} + kΛndΛ (N) become mΛkΛndə (V). suffix {-In}: NPD klΛmbI (N) become klΛmbIn (V). suffix {-ē }: SP: tΛbIng (V) become tΛbIngΛ (V) and NPD: Jǝlǝmǝ (N) become JǝlǝmΛtē (N). The similarity prefix {mə-}: NPD and SP: {mə-} + jΛlΛn (N) become məjΛlΛn (V),. Prefix {m-} NP and SP: {m-} + bʊbʊh (N) become mʊbʊh (V). suffix {-Λŋ} NP and SP: sΛmpΛt (N) + {-Λŋ}→ become sΛmpΛtΛŋ (V). Suffix {-In} NP and SP: nɒt (V) + {-In} → become nɒtIn (V). keyword : Derivational Morpheme, Inflectional Morpheme, Nusa Penida Dialect and Sepang dialect.